Mental health plan for workers of the London Nightingale Hospital: following the evidence to support staff. Issue 2 (29th October 2020) - Greenberg, Neil; Cooke, J; Sullivan, E; Tracy, D K
Abstract : The COVID-19 pandemic has extracted an enormous physical health toll on many millions worldwide, and the wider societal impact from economic turmoil, unemployment, social isolation and so forth continue to be measured. A less explored aspect has been the psychological impact on treating healthcare staff, with emerging evidence of 'moral injury' and mental illness for some. This review explores the evidence base for implementing a tiered model of care to minimise this and foster 'post-traumatic growth', and describes the authors' implementation of this in the London Nightingale hospital, with lessons for the armed forces.